Penerjemahan Novel Anak dari Bahasa Inggris ke Bahasa Indonesia: Analisis Kesalahan Penerjemahan dalam Novel Diary Si Bocah Tengil yang Diterjemahkan oleh Ferry Halim - Dewi Susanti Siahaan (Indonesian Journal of Applied Linguistics Review, 2016)
This study aimed to analyze the forms of unequivalence, translation procedures andtypes of translation error in Diary of a Wimpy Kid Noveltranslated from English to Bahasa Indonesia. It was a qualitative research with content analysis method conducted in 2015. The data were collected through a thorough reading and analyzing as well both source text and target text that the sentences that has error(s) in it. The data analysis and interpretation indicates that the deviation found to be the most (64,3%), followed by modification (12,8%), omission (12,8%),addition (5,72%), inversion (4,3%) and The findings lead to the recommendation to understand things beyond the text, practice continuous critic analysis learning method with various texts in the class in order to sharpen the ability to translate.